Detailed analysis of Ga-rich current pathways created in an n-Al0.7Ga0.3N layer grown on an AlN template with dense macrosteps. (30th November 2020) - Nagasawa, Yosuke; Hirano, Akira; Ippommatsu, Masamichi; Sako, Hideki; Hashimoto, Ai; Sugie, Ryuichi; Honda, Yoshio; Amano, Hiroshi; Akasaki, Isamu; Kojima, Kazunobu; Chichibu, Shigefusa F.
Abstract: To clarify the behavior of the AlGaN in 20 nm wide Ga-rich current pathways in an n-AlGaN layer, which assists carrier localization in AlGaN-based light-emitting diodes, we performed a detailed analysis using an n-Al0.7 Ga0.3 N layer on AlN with dense macrosteps on a 1.0° miscut sapphire substrate. Energy-dispersive X-ray spectra, obtained using cross-sectional scanning transmission electron microscopy calibrated by Rutherford backscattering and cross-sectional cathodoluminescence spectra, indicated that AlN mole fraction in the Ga-rich current pathways was nearly ~2/3. This result is consistent with those of other research groups, suggesting that metastable Al2/3 Ga1/3 N is created in Ga-rich current pathways.